2019
DOI: 10.1108/ejm-02-2018-0104
|View full text |Cite
|
Sign up to set email alerts
|

Ethical attribute and brand concept congruity enhances brand evaluations

Abstract: Purpose This paper aims to examine to what extent congruity between ethical attributes (i.e. product attributes with positive implications for the environment, human rights, social issues and animal welfare) and brand concept (i.e. the unique meaning associated with a brand in consumers’ minds) influences consumers’ evaluations of brands offering ethical attributes. Design/methodology/approach Four studies involving North American consumers empirically tested the moderation effect of brand concept on consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Although convenience sampling restricts the generalisability of the result, yet previous studies (Chauhan et al , 2019; Yadav and Pathak, 2016) have recommended adopting this technique owing to the lack of a proper sampling frame. In concurrence with Tofighi et al (2020) and Sadiq et al (2020), data for this research was collected through the online survey using Amazon Mechanical Turk platform on 7th January 2020. The inclusion criteria for selection of the respondent was that he/she should be an adult, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Although convenience sampling restricts the generalisability of the result, yet previous studies (Chauhan et al , 2019; Yadav and Pathak, 2016) have recommended adopting this technique owing to the lack of a proper sampling frame. In concurrence with Tofighi et al (2020) and Sadiq et al (2020), data for this research was collected through the online survey using Amazon Mechanical Turk platform on 7th January 2020. The inclusion criteria for selection of the respondent was that he/she should be an adult, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…and symbolic ethical attributes (such as public welfare, social responsibility, etc. ; Bodur et al, 2014;Tofighi et al, 2020). Consumers' purchasing decisions are based on evaluations and needs for product-specific attributes.…”
Section: Ethical Attributes Of Farmer-assisting Agricultural Productsmentioning
confidence: 99%
“… Bezençon et al (2020) have revealed that purchasing products with ethical attributes (e.g., EcoConscious or No Child Labor statement) can reflect their concerns and support for social or ethical issues, but has nothing to do with the function of the product itself. Thus, ethical attributes also refer to symbolic ethical attributes to a certain extent ( Peloza et al, 2013 ; Sama et al, 2018 ; Hindsley et al, 2020 ; Tofighi et al, 2020 ; Das et al, 2021 ; Wang et al, 2021 ; Salam et al, 2022 ; see Table 1 ). Unlike previous research, Bodur et al (2014) believed that products with ethical attributes also have functional benefits at the same time.…”
Section: Theoretical Backgroundsmentioning
confidence: 99%
“…Consumers prefer the reduced levels of uncertainty brought by congruence as less uncertainty facilitates the processing of new information (Schwarz, 2004 ). Consequently, the higher degree of fluency that arises in the case of congruence triggers more favorable product evaluations (Winkielman et al, 2015 ; see also Tofighi et al, 2020 for a more recent example of congruence on brand perception).…”
Section: Theoretical Backgroundmentioning
confidence: 99%